Information system development - Aragon, Gustavo; Linger, Henry; Lang, Michael; Barry, Chris; Schneider, Christoph; Jose Escalona, Maria (Springer International Publishing, 2014)
Information System Development-Improving Enterprise Communication are the collected proceedings of the 22nd  International Conference on Information Systems Development: Improving Enterprise Communication-ISD 2013 Conference, held in Seville, Spain. It follows in the tradition of previous conferences in the series in exploring the connections between industry, research and education. These proceedings represent ongoing reflections within the academic community on established information systems topics and emerging concepts, approaches and ideas. It is hoped that the papers herein contribute towards disseminating research and improving practice. The conference tracks highlighted at the 22nd International Conference on Information Systems Development (ISD 2013) were: Applications Data and Ontologies End Users Enterprise Evolution Industrial cases in ISD Intelligent Business Process Management Model Driven Engineering in ISD New Technologies Process Management Quality